Glacial ring forms on Axel Heiberg Island, Nunavut, Canada - S. M. Hibbard; S. M. Hibbard; G. R. Osinski; E. Godin; C. Andres; A. Kukko; A. Kukko; S. Chartrand; A. Grau Galofre; A. M. Jellinek; W. Boucher (The Cryosphere)
Ring forms are a type of landform consisting of a series of ridges and troughs with a circular, sinuous, and anastomosing morphology. This striking landform was initially identified in the Canadian High Arctic on the south coast of Devon Island, Nunavut, Canada. Here, we report on the identification of ring forms near Mokka Fiord on Axel Heiberg Island, Nunavut, Canada. Utilizing field observations, ultra-high-resolution light detection and ranging (lidar), and ground-penetrating radar (GPR), we characterize and compare the morphometry and sedimentology of ring forms at Mokka Fiord with other similar periglacial, paraglacial, and glacial landforms. The Mokka Fiord ring forms range in diameter from 6 to 37 m and reach up to 1.5 m in height and are composed of clast-rich glaciofluvial sediment and till. Based on both regional and local observations, results from nearby field investigations of glacial outwash plains on Axel Heiberg Island, and comparisons to other periglacial and glacial features sharing a similar morphology, we interpret Mokka Fiord ring forms as glacial in origin. Specifically, we propose Mokka Fiord ring forms are ice-marginal glaciofluvial kame terraces formed from the passive ablation of buried glacial ice, leading to the formation of hummocky ring forms. This formation mechanism supports a predominantly polythermal glacial environment with limited water supply throughout much of the Holocene.